The structure of heat-resisting alloy modified by thermal treatment and alloyed by rhenium and lanthanum; IOP Conference Series: Materials Science and Engineering; Vol. 156 : Materials and Technologies of New Generations in Modern Materials Science - Kozlov E. V.; Popova N. A.; Nikonenko E. L. Elena Leonidovna; Kondratyuk А. А. Alexey Alekseevich; Kuznetsov M. E.; Klopotov A. A. (2016, 2016)
Title screen